Implementasi Nilai-Nilai Islam Dalam Pendidikan Karakter Di Pondok Pesantren Darunnajah Jakarta - Duna Izfanna (Edukasiana: Journal of Islamic Education, 2023)
Abstract This research aims to describe how Pondok Pesantren, a unique Islamic eduation system implemented and contributed substantially to the character education of its students. 12 teachers and 24 students of Pondok Pesantren Darunnajah participated in focus group discussions and were observed. Findings suggest that the character education implemented in Pondok Pesantren Darunnajah laid on Islamic values as its ultimate philosophy. The majority of teachers and students reported that the Pondok educates and develops students’ character by infusing knowledge, providing conditions or environment, and giving chances to practice.